Paternal postpartum depression's relationship to maternal pre and postpartum depression, and father-mother dyads marital satisfaction: A structural equation model analysis of a longitudinal study - Barooj-Kiakalaee, Ozra; Hosseini, Seyed-Hamzeh; Mohammadpour-Tahmtan, Reza-Ali; Hosseini-Tabaghdehi, Monirolsadate; Jahanfar, Shayesteh; Esmaeili-Douki, Zahra; Shahhosseini, Zohreh (Journal of affective disorders, 2022)
•We examined the relationship of paternal postpartum depression with prenatal and postpartum depression of mothers and couples' marital satisfaction.•The primary basis of data analysis was structural equation modeling.•The results showed that maternal marital satisfaction and maternal postpartum depression were associated with paternal postpartum depression.•the quality of marital relationships and mothers' perinatal mental health are necessary to promote fathers' mental health. Fathers' depression is an understudied subject, and the increasing participation of fathers on the care of their children, this is an issue of great importance. This study aimed to determine the relationship of paternal postpartum depression with prenatal and postpartum depression of mothers and their marital satisfaction. This longitudinal study was conducted among 352 expecting couples in 28–40 weeks of pregnancy and 6–8 weeks after delivery from April to September 2019. Eligible participants were selected from primary health care centers in northern Iran using a two-stage sampling method. Socio-demographic information, Edinburgh Postpartum Depression Scale, and ENRICH Couple Scale were used for data collection. The primary basis of data analysis was cross-lagged structural equation modeling to explore the underlying mechanism for paternal postpartum depression. The results showed that a) maternal prenatal depression indirectly (βstand = 0.32, p = 0.004); b) maternal postpartum depression directly (βstand = 0.56, p <0.001); c) paternal prenatal depression indirectly (βstand = 0.11, p = 0.028) were associated with paternal postpartum depression. Also, marital satisfaction directly (βstand = -0.19, p = 0.002) and indirectly (βstand = -0.11, p = 0.007) had a relationship to paternal postpartum depression. Culturally-sensitive measures of marital satisfaction, especially in conservative context of developing countries, along with self-reported data of psychological problems may lead to under-reported findings. The major contribution of marital satisfaction and maternal depression during prenatal period on the paternal postpartum depression, emphasizes on the prenatal period as the ideal time for fathers' mental health improvement.